Effectiveness of overgloves in preventing cross contamination after exposure to staphylococcus aureus - Molina, Roxan
Overgloving is one measure to control cross contamination where an overglove is worn over an examination glove before touching any environmental surface. It reduces the consumption of expensive treatment gloves and glove changing. This study aimed to determine the effectiveness of using an overglove as a barrier in preventing cross contamination through comparing fluid permeability and bacterial penetrability of FDA-approved overgloves and commercially available kitchen plastic overgloves. METHODS: Dye permeability and bacterial penetration were the methods for this study. Ten samples from each of the three (3) brands of overgloves were used: two commercially available and one FDA-approved. In the permeability test, 0.2% erythrosine dye solution was dropped inside the middle finger while water was dropped inside the index finger of each overgloves. The outside area was washed with distilled water after 30, 60, 90 and 120 minutes. The dye and water (washing) was read with a spectrophotometer. In the bacterial penetrability test, index fingers were filled with distilled water serving as the control and middle fingers were filled with Staphylococcus Aureus suspension. Each finger was imprinted on blood agar plates after 15, 30, 45 and 60 minutes. RESULTS: The degree of fluid permeability test showed a statistical difference between the FDA-approved overgloves and the commercially available overgloves. No significant difference on the different time intervals. With the bacterial permeability test, all brands, whether FDA-approved or commercially available overgloves, showed positive bacterial penetration. However, the FDA-approved ovewrgloves showed the highest percentage of the presence of bacteria. CONCLUSION: This study concludes that there are certain brands of overgloves that are effective as a barrier for cross contamination after being subjected to dye and bacterial penetrability test.